Avaliação da enzima paraoxonase tipo 1 no plasma seminal e sua expressão de RNAm dos tecidos das gônadas em suínos - Lucca, Matheus Schardong (2016)
The seminal plasma is particularly important in sperm protection against damage caused by reactive oxygen species (ROS). The paraoxonase type 1 (PON1) is a multi-enzymatic complex with antioxidant properties, preventing the increase of ROS quantities, thus protects cell membranes and neutralizes the effects of lipid oxidation. The objective of this study was to correlate the influence of PON1 activity with the CASA system parameters and sperm viability (membrane integrity acrosome integrity, functionality of mitochondria and DNA fragmentation) of swine semen in natura, and investigate the PON1 expression (mRNA) in testicle and epididymis (head, body and tail) tissue of boars. The sperm fraction (FE) presented the major PON1 activity and males 81, 80 and 79 (P<0.05) showed the highest enzyme activity. But, when comparing the differences between the ejaculate samples, our study showed differences (P<0.05) between males 81 and 92 in FE and sperm post fraction (PF). However, when the ejaculated was diluted (1:1), it has presented 44% average reduction in the activity of PON1. The activity of PON1 in FE showed positive correlation with sperm concentration, curvaceous distance, curvy velocity and DNA integrity (P<0.05), and also showed negative correlation with straightness and linearity parameters advised by the CASA system. The mRNA expression was observed only in the body portion of the epididymis. The FE is the part of the ejaculate that more PON1 activity and presented the parameters DCL, VCL, STR and LIN, together, with concentration and sperm viability (integrity of DNA) are those who showed the greatest association with the enzyme. Already the PON1 was only expressed (Mrna) in the body of epididymis pig breeder.